Fermented Rubber Seed Kernel with Yeast in the Diets of Tropical Lactating Dairy Cows: Effects on Feed Intake, Hematology, Microbial Protein Synthesis, Milk Yield and Milk Composition - Thanaporn Ouppamong; Nirawan Gunun; Chayapol Tamkhonburee; Pichad Khejornsart; Chatchai Kaewpila; Piyawit Kesorn; Thachawech Kimprasit; Anusorn Cherdthong; Metha Wanapat; Sineenart Polyorach; Suban Foiklang; Pongsatorn Gunun (My University, 2022)
The objective of the present study was to analyze the effects of yeast-fermented rubber seed kernels (YERSEK) on the feed intake, hematology, microbial protein synthesis, milk yield, and milk composition in dairy cows. Six crossbred Holstein Friesian (HF) × Thai lactating dairy cows with 110 ± 10 days in milk were randomly assigned to three different amounts of YERSEK at 0%, 10%, and 20% in a concentrate mixture using a 3 × 3 repeated Latin square design. Cows were fed with concentrate diets at a concentrate-to-milk yield ratio of 1:1.5, with rice straw fed ad libitum. The inclusion of YERSEK did not adversely affect feed intake, nutrient intake, or digestibility (p > 0.05), whereas ether extract intake and digestibility linearly increased in dairy cows receiving YERSEK (p < 0.01). Increasing YERSEK levels did not adversely affect blood urea nitrogen (BUN) levels, hematological parameters, or microbial protein synthesis (p > 0.05). Supplementation of YERSEK did not influence milk production, lactose, or protein levels (p > 0.05). However, milk fat and total solids decreased linearly (p < 0.05) with the addition of YERSEK. In conclusion, in a concentrate diet, YERSEK could be used as a protein source without negative effects on feed intake, digestibility, hematology, microbial protein synthesis, or milk yield. However, it reduced the milk fat and total solids of tropical lactating dairy cows.
Keywords: Latin square; Total dissolved solids; Ruminant Nutrition and Digestive Physiology